PENGARUH KARAKTERISTIK DEWAN DIREKSI DAN KOMISARIS TERHADAP FINANCIAL RESTATEMENT - I Dewa Ardana; Sany Sany (Business Accounting Review, 2021)
Financial restatements represent a serious failure in financial reporting, and cansignificantly affect many organizations, institutions, investors, markets and regulators.This study aims to analyze the effect of board and commissioner analysis on financialrestatements. The population in this study are financial sector companies listed on theIDX from 2016-2020. With a total of 76 companies (www.idx.co.id). The data analysistechnique that will be used uses a quantitative approach by performing logistic regressionanalysis to see the effect of the independent variables on the variables. The results showthat Hypothesis H1 is accepted, where board size has an effect on financial restatements.Hypothesis H2 is accepted, where board independence has a negative effect on financialrestatements. Hypothesis H3 is rejected, where women on board have no effect onfinancial restatements.